Reading power, violence, and gender anxiety in Shakespeare’s Macbeth: Re-reading the play in a contemporary context - AlAli, Rommel Mahmoud; Alomari, Mohammad Ahmad Shehadeh; Sagir Khan, Aayesha; Abdullatif, Ali (Research Journal in Advanced Humanities, 2026)
This manuscript argues that Macbeth is best understood not simply as a tragedy of vaulting ambition, but as a dense dramatic inquiry into the unstable relationship among sovereign power, spectacular violence, and gender anxiety. Through close reading and interdisciplinary synthesis, the essay shows that the play imagines kingship as a problem of legitimacy that is never fully separable from force. Duncan’s rule depends upon military violence, Macbeth’s rise converts publicly sanctioned violence into terroristic self-preservation, and Malcolm’s restoration remains shadowed by the same structures of martial masculinity that enabled the usurpation in the first place. At the level of imagery and embodiment, Macbeth repeatedly stages wounded, violated, and threatened bodies: the bleeding captain, the floating dagger, the murdered sleepers, Banquo’s ghost, Lady Macduff and her child, Macduff’s “pretty chickens,” and Lady Macbeth’s compulsively washing hands. These bodies are not incidental. They are the means by which political order is made visible, contested, and internalized.The essay further contends that gender anxiety is not a secondary theme but one of the principal motors of the tragedy. Lady Macbeth’s prayer to be “unsexed,” the witches’ bearded bodies, the recurrent language of milk, gall, birth, and children, and the repeated testing of manhood all indicate that Macbeth locates political crisis in unstable fantasies about sex, gender, and reproduction. Masculinity in the play requires constant proof; femininity is idealized as nurture and simultaneously feared as a source of disorder; and reproductive futurity becomes a field of intense violence. A contemporary re-reading therefore reveals Macbeth as an uncannily durable drama of authoritarian desire, toxic masculinity, crisis rhetoric, charisma, media spectacle, and the destruction of intimate life by militarized politics.To make that contemporary argument, the essay brings established Shakespeare criticism into conversation with broader theoretical work on sovereignty, trauma, affect, performativity, and adaptation, while also drawing on twenty sources from Ianna Journal of Interdisciplinary Studies as an interdisciplinary bridge to current debates on women’s empowerment, media representation, digital democracy, marginalization, gendered labor, trauma, and collective violence. The conclusion is that Macbeth endures because it shows how power secured through violence produces not mastery but psychic disintegration, institutional fragility, and a permanently anxious theater of gender.